A new frog of the Leptodactylus fuscus species group (Anura: Leptodactylidae), endemic from the South American Gran Chaco - Schneider, Rosio G.; Cardozo, Dario E.; Brusquetti, Francisco; Kolenc, Francisco; Borteiro, Claudio; Haddad, Célio [UNESP]; Basso, Nestor G.; Baldo, Diego (PeerJ, 2019)
A new species of Leptodactylus frog (Anura: Leptodactylidae) from the South American Gran Chaco, morphologically similar and previously confused with the widespread Leptodactylus mystacinus, is described through the use of multiple sources of evidence (molecular, external morphology, coloration, osteology, bioacoustics, and behavior). The phylogenetic analysis with partial sequences of mitochondrial rDNA genes (12S and 16S) recovered the new species within the L. fuscus group, being highly divergent (>3% genetic distance in 16S). The new species was recovered as sister taxa of L. mystacinus, from which it is distinguished by tympanum coloration, cephalic index, dorsum and legs coloration, and some osteological differences in nasals and prevomers. This new frog is characterized by a moderate body size (SVL 46.80–66.21 mm), distinctive color pattern (reddish dorsal surfaces of body with noticeable black stripes in the dorsolateral folds), a circular and dark tympanum with dark tympanic annuli, and behavior of males that call on top of fallen logs and tree branches close to the ground.
Keywords: Bioacoustics; Leptodactylinae; Molecular systematics; Morphology; Taxonomy